2020
DOI: 10.1177/0022034520939013
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 Controls Periderm and Rugae Development to Inhibit Oral Adhesions

Abstract: In humans, ankyloglossia and cleft palate are common congenital craniofacial anomalies, and these are regulated by a complex gene regulatory network. Understanding the genetic underpinnings of ankyloglossia and cleft palate will be an important step toward rational treatment of these complex anomalies. We inactivated the Sry (sex-determining region Y)–box 2 ( Sox2) gene in the developing oral epithelium, including the periderm, a transient structure that prevents abnormal oral adhesions during development. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Injecting p53 −/− embryos with sertad4 MO generated the same morphological abnormalities, indicating that the deformities observed in morphants are not caused by up‐regulation of the p53‐dependent apoptotic pathway 26 (Figure A). Further, since Sox2 regulates development of the palate rugae, and a loss of this palate signalling centre may contribute to clefting 27 . Thus, we investigated the expression of sox2 and found it was significantly down‐regulated in sertad4 knockdown zebrafish models at 96hpf (Figure B).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Injecting p53 −/− embryos with sertad4 MO generated the same morphological abnormalities, indicating that the deformities observed in morphants are not caused by up‐regulation of the p53‐dependent apoptotic pathway 26 (Figure A). Further, since Sox2 regulates development of the palate rugae, and a loss of this palate signalling centre may contribute to clefting 27 . Thus, we investigated the expression of sox2 and found it was significantly down‐regulated in sertad4 knockdown zebrafish models at 96hpf (Figure B).…”
Section: Resultsmentioning
confidence: 97%
“…29 The sertad4 knockdown in our zebrafish model induced mandibular deficiency, heart failure and down-regulation of Sox2 protein which had been implicated in various processes of early embryogenesis. 27,30 SYT14 participates in pathomechanical neurodegeneration and contributes to abnormal neurodevelopment. 31 Previous studies found that the expression of Syt14 was highly restricted to the mouse heart and testis but absent in the brain, suggesting that Syt14 may be involved in membrane trafficking in specific tissues other than the brain.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that HMGN2 interacts with Pitx2 and Sox2 to form an inactive complex to inhibit Pitx2 and Sox2 DNA-binding activity ( 23 , 24 , 25 , 39 ). Dlx2 is required for craniofacial and tooth development, and we have shown that Pitx2 and Lef-1 regulate the Dlx2 promoter ( 23 , 40 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…We next determined if dental epithelial cell proliferation was affected in the lower incisor of Hmgn2 −/− embryos. We have previously shown that Pitx2 and Lef-1 control dental epithelial cell proliferation and differentiation ( 24 , 25 , 49 ). Our hypothesis is that the loss of Hmgn2 would increase the transcriptional activity of factors involved in dental epithelial cell proliferation and differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation